Two Consecutive Days of Extreme Conditioning Program Training Affects Pro and Anti-inflammatory Cytokines and Osteoprotegerin without Impairments in Muscle Power - Tibana, Ramires A.; de Almeida, Leonardo M.; Frade de Sousa, Nuno M.; Nascimento, Dahan da Cunha; Neto, Ivo V. de Sousa; de Almeida, Jeeser A.; de Souza, Vinicius C.; Lopes, Maria de Fátima T. P. L.; Nobrega, Otávio de Tolêdo; Vieira, Denis C. L.; Navalta, James W.; Prestes, Jonato (Frontiers in Physiology, 2016)
Abstract The aim of this study was to investigate the effects of two consecutive Crossfit® training sessions (24 hours apart) designed to enhance work-capacity that involved both cardiovascular and muscular exercises on cytokines, muscle power, blood lactate and glucose. Nine male members of the CrossFit® community (age 26.7 ± 6.6 years; body mass 78.8 ± 13.2 kg; body fat 13.5 ± 6.2 %; training experience 2.5 ± 1.2 years) completed two experimental protocols (24 hours apart): 1) strength and power exercises 2) gymnastic movements and 3) metabolic conditioning as follows: 10 min of as many rounds as possible (AMRAP) of 30 double-unders and 15 power snatches (34kg). The same sequence as repeated on session 2 with the following metabolic conditioning: 12 min AMRAP of: row 250m and 25 target burpees. Serum interleukin-6 (IL-6), IL-10 and osteoprotegerin were measured before, immediately post and 24 h after training 1, immediately post, 24 h and 48 h after training session 2. Peak and mean power were obtained for each repetition (back squat with 50% of 1 repetition maximum) using a linear position transducer measured before, immediately post and 24 h after training 1, immediately post and 24 h after training session 2. Blood lactate and glucose were measured pre and immediately post-exercise sessions 1 and 2. Although both sessions of exercise elicited an significant increase in blood lactate (1.20 ± 0.41 to 11.84 ± 1.34 vs 0.94 ± 0.34 to 9.05 ± 2.56 mmol/l) and glucose concentration (81.59 ± 10.27 to 114.99 ± 12.52 vs 69.47 ± 6.97 to 89.95 ± 19.26 mg/dL), exercise training 1 induced a significantly greater increase than exercise training 2 (p ≤ 0.05). The training sessions elicited significant changes (p ≤ 0.05) in IL-6, IL-10 and osteoprotegerin concentration over time. IL-6 displayed an increase immediately after training session 1 [197 ± 109%] (p = 0.009) and 2 [99 ± 58%] (p = 0.045). IL-10 displayed an increase immediately after only training session 1 [44 ± 52%] (p = 0.046), and decreased 24 and 48 h following training session 2 ( 40%; p = 0.018) as compared to pre-exercise values.